Organoleptic Quality of Nutrient Dense Noodles Based on Local Food as an Alternative to Emergency Food - Vinny Pratiwi,; Irma Eva Yani; Sri Darningsih (POLTEKKES KEMENKES PADANG, 2023)
Noodles are one of the foods that are accepted not only by adult but also by children. Wet noodles are one type of noodle that contains high carbohydrates but low protein. There is a gap in the minimum protein content in the type of wet noodles commonly sold on the market, which is 8,4 grams. Therefore, it is necessary to add a protein source in the form of dry rebon shrimp flour. The purpose of this research was to determine the best treatment and organoleptic quality of nutrient dense noodles substituted with dried rebon shrimp flour. This research is experimental research in the field of food technology with a completely randomized design with one control, three treatment, and two repetitions. The organoleptic test was carried out at the Food Science Laboratory, Department of Nutrition at Polytechnic Health of Padang. The research was conducted from March 2020 to April 2021. Data analysis using the Kruskal Wallis test was followed by the Mann Whitney test if there were significant differences. The results of the Kruskal Wallis test showed significant differences in the colour, scent, flavor, and texture of wet noodles. The result found that the best treatment was a ratio of 75:25 grams. It is recommended to use substitution of 25 grams of dry rebon shrimp flour in making wet noodles.